Justice Across Generations - Reed, Ryan. author. aut Link
XI, 177 p. 1 illus.
Keywords: This book presents a contractualist theory of intergenerational justice that avoids deficiencies in existing IGJ theories, e.g., the non-identity problem and the under-defining of "generations." The inability of social contract theory to provide a thorough accounting of justice between generations has been called an embarrassment and rightly so. That said, serious attempts have been made from a variety of contract perspectives to rectify the approach’s shortcomings in the area of intergenerational justice. One of the most prominent contract theorists, John Rawls, attempted to address justice between generations in his theory via his just savings principle, but both versions of it were met with stinging criticism. As the climate crisis, among other challenges, presses the issue of justice for future generations, the authors believe that intergenerational justice is something that social contract theory should and can address. Specifically, they present a Rawlsian approach that begins with a clarified understanding of what is meant by “generations,” and proceeds from there to modify generational knowledge constraints in the original position. The authors then draw upon the concept of indirect reciprocity to round out an argument for a Rawlsian principle of justice between generations: intergenerational fair equality of opportunity. They then apply their intergenerational justice theory to five major public policy areas. Ryan Reed is Associate Professor of Political Science at Bradley University. Christopher R. Hallenbrook is Associate Professor of Political Science and L.G. Chaffee Endowed Chair of Global and Comparative Politics at California State University Dominguez Hills.